Thermal comfort in lower economic groups: The applicability of the ASHRAE-55 adaptive standards in informal settlements and refugee camps - Ibrahim, Rawia (2025)
Thermal comfort is influenced by climate, expectations and adaptation opportunities. Hence the emergence of adaptive thermal comfort standards. Unfortunately, international adaptive standards and much of the underlying literature, are based on data collected from middle-income individuals in office or apartment blocks, raising the question of their validity in other contexts. This paper is the first large-scale investigation of the applicability of these standards to populations living in refugee/displacement camps, to establish whether comfort theory needs to be modified for such populations. This was achieved through highly difficult, data collection in camps in Jordan, Djibouti, Ethiopia and Peru. The data collected consists of 1982 rows of personal variables and concurrent environmental measurements. From these, the thermal comfort boundaries of the displaced were found to be wider (13K) than suggested in prevalent standards (8K). A new mathematical model of thermal comfort for such groups is hence developed. The results expand our understanding of comfort theory to include an understudied population and will be useful for those responsible for shelter for the currently 120M displaced, as they now allow rational design standards to be set. A tool based on the new model is currently being applied by aid agencies in camps in Afghanistan.